The Burden of Illness in Patients with Moderate to Severe Chronic Obstructive Pulmonary Disease in Canada - M Reza Maleki-Yazdi; Suzanne M Kelly; Sy S Lam; Mihaela Marin; Martin Barbeau; Valery Walker (Canadian Respiratory Journal)
INTRODUCTION: No recent Canadian studies with physician- and spirometry-confirmed diagnosis of chronic obstructive pulmonary disease (COPD) that assessed the burden of COPD have been published.